PLATO'S REPUBLIC AND THE INDO-EUROPEAN PENTADIC IDEOLOGY. (December 2020) - Allen, Nick
Abstract : Similarities between ancient Greek philosophy and Indian philosophy have long been recognized and are usually ascribed to East-West contact. However, when similarities are recognized between Greek and Indian poetic diction or, more generally, between the myths and the poetry of the two cultures, they are often ascribed to Indo-European common origin; and one asks whether the same explanation could apply in philosophy. The two types of explanation are not incompatible, for a remote common origin could have been followed by one or more periods of interaction. Nevertheless, it is worth seeing how far an explanation of common origin can be pressed before falling back on the explanation of contact.